Nuclear DNA content in two Sphaeriidae species from Southern Chile (Bivalvia: Veneroida). (3rd April 2017) - Jara-Seguel, Pedro; Parada, Esperanza; Peredo, Santiago; Palma-Rojas, Claudio; von Brand, Elisabeth
ABSTRACT: The family Sphaeriidae is a group of cosmopolitan freshwater clams that inhabit temporary and permanent fluvial and lacustrine environments around the world. In Chile, Sphaeriidae is represented by 11 species belonging to the genera Musculium, Pisidium and Sphaerium . In this study, the nuclear DNA content (or 2C-value) of Musculium argentinum (d'Orbigny, 1835) and Pisidium llanquihuense Ituarte, 1999 was estimated for the first time. Musculium argentinum showed a 2C-value of 3.7 ± 0.38 pg, whereas P. llanquihuense showed a 2C-value of 3.57 ± 0.36 pg. These 2C-values are within the range previously reported for Sphaeriidae (2.35–5.7 pg), which includes diploids and polyploids, amounting to 13 of the species examined around the world. Of the cytological data available for the family, the nuclear DNA content can have a unifying role in understanding the magnitude of the chromosome polymorphisms within this polyploid complex.